Deep Space Commodities Exploration, Production and Trading (Springer International Publishing, 2018)
Welcome to the new space economy... Space is open for business! The dawn of a new space race led by private sector entrepreneurs is upon us thanks to the USA Space Act 2015 and technology advances like SpaceX rockets, which have greatly reduced the cost of space flight. For the first time in history, the advances in both technical and legal infrastructure have opened up exciting opportunities that are already driving the commercial exploration of deep space commodities, Space tourism with Virgin Galactic, and the serious planning for the colonisation of our Moon and Mars. Tom James, a leading commodity and energy market practitioner and author, has brought together top professionals in academia, astropolitics, space engineering, and space law to explore the exciting opportunities and challenges businesses face in the new off-planet economy. With quadrillions of dollars of mineral wealth and frozen water within our reach, the stakes may be high, but so are the rewards. So pack your bags, fasten your oxygen mask and let's get ready to boldly take business where business has not gone before...